Determinants of bank performance: conventional versus Islamic - Nabilah Rozzani,; Rashidah Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Using CAMELS rating to measure bank performance, the present study compares the performance estimates for Islamic banks with conventional banks operating in Malaysia from 2008 to 2011. The present study further identifies the determinants affecting the performance of conventional and Islamic banks in Malaysia. Using a sample of 19 conventional banks and 16 Islamic banks, the results indicate that the levels of composite performance achieved by both conventional and Islamic banks in Malaysia are very similar. Furthermore, it is observed that the performance of conventional banks will improve following the reduction of operational costs, while the performance of Islamic banks will improve following the reduction of bank size and an increment of credit risk.